460 CHAPTER 7 Counting and Combinatorics
(Inductive step) Choose n > no, and assume n E T. Now, prove that n + 1 E T. Begin
by setting
(x + y)n+l = (x + y)(x + y)n.
By the inductive assumption, this is
n
(X -y)n+l = (X + y) * • C(n, i) Xn-i yi
i=O
= x 1 C(n, i) xn-i yi) + y C(n, i) xn-i yi)
ni=0 i=O
n
= C(n, O)xn+l + - C(n, i) xn-i+l yi
i=1
n-1
- C(n, i) Xn-i yi+l + C(n, n)yn+
1
i=O
Next, replace i by i - 1 in the third term, giving
n-1 n
Y C(n,i)xn-i yijl =: C(n, i - 1) xn-i+l yi
i=O i=t
This makes the two sums start at the same value so that they can be added term by term to
get
n
S(C(n, i) +4 C(n, i - 1)) xn-i+t yi
By Pascal's Identity, the sum becomes
n
Y' C(n + 1, i) xn-i+l yi
i=1
Combining these results gives
n
(X + y)n+l - yn+l -+ Z C(n + 1, i) Xn-i+l y i +t xn+
i=1
n+1
S L C(n ± 1, i)xn+l-i yi
i=O
Therefore, n + 1 E T.
By the Principle of Mathematical Induction, T = N. U
Knowing the form of the coefficients of (x + y)n allows some interesting results to be
proven.
Theorem 6. For n E N,
2n = C(n, O) + C(n, 1) - ' C(n, n)